RESEARCH INTO BILINGUAL DICTIONARIES IN VIETNAM - Nhung, Hoang Thi (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4610, 2020)
This article provides an overview of the situation of bilingual dictionary research in Vietnam according to the different approaches of lexicography. The studies are divided into three phases. At each phase, they are arranged according to approaches. Therefore, a panorama of the research situation is clearly and systematically described. Thereby, the reader can see the achievements as well as the unrealized fields of bilingual lexicographers.